Associations of coagulation factor X and XI with incident acute coronary syndrome and stroke: A nested case‐control study. (31st August 2021) - Chen, Huiting; Shen, Miaoyan; Niu, Rundong; Mu, Xuanwen; Jiang, Qin; Peng, Rong; Yuan, Yu; Wang, Hao; Wang, Qiuhong; Yang, Handong; Guo, Huan; He, Meian; et al.
Abstract: Background: Coagulation cascade contributes to thrombotic and hemorrhagic diseases, but it remains unclear whether coagulation factors X (FX) and XI (FXI) levels are associated with cardiovascular diseases. Objective: To evaluate prospective associations of FX and FXI levels with incident acute coronary syndrome (ACS), stroke, and their subtypes (acute myocardial infarction, unstable angina, ischemic stroke, and hemorrhagic stroke). Methods: We performed a nested case‐control study ( n = 1846) within the Dongfeng‐Tongji cohort from 2013 to 2016 matched on age (within 1 year), sex, and sampling date (within 1 month) by incidence density sampling, and measured plasma FX and FXI levels by enzyme‐linked immunosorbent assay. FX and FXI levels were categorized into three groups (low, <25th; middle, 25th to <75th; and high ≥75th percentiles) according to distributions, and conditional logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: After adjustment for traditional cardiovascular risk factors, compared with middle groups, the OR (95% CI) in high levels of FX and FXI were 1.11 (0.79–1.56) and 0.96 (0.68–1.36) for incident ACS, and 1.01 (0.63–1.62) and 1.72 (1.14–2.60) for incident stroke, respectively. As for subtypes of ACS and stroke, only high FXI levels were significantly associated with incident ischemic stroke (OR 1.66, 95% CI 1.05–2.65). Moreover, all associations remained steady after additional adjustment for platelet and leukocyte. Conclusion: FXI levels were associated with a greater risk of incident ischemic stroke but not hemorrhagic stroke or ACS. FX levels were not associated with incident ACS or stroke.